Probiotics for the prevention of gestational diabetes mellitus: A meta-analysis of randomized controlled trials - Xue Li; Luwen Zhang; Yuanqi He; Dandan Zhang; Shihong Zhang (Biomolecules & Biomedicine, 2024)
Changes of intestinal microbiota have been shown to be involved in the development of gestational diabetes mellitus (GDM). We performed a meta-analysis to systematically evaluate the potential role of probiotics for the prevention of GDM. Systematic literature search was performed in electronic databases including PubMed, Cochrane library, Embase, Web of Science, Wanfang, and China National Knowledge Infrastructure (CNKI) to obtain relevant randomized controlled studies. A random-effects model was used to pool the results by incorporating the impact of the potential heterogeneity. Meta-regression and subgroup analyses were conducted to evaluate the source of heterogeneity. Fourteen studies involving 3527 pregnant women were included. Results showed that probiotics significantly reduced the incidence of GDM as compared to control (risk ratio [RR]: 0.71, 95% confidence interval [CI]: 0.52–0.96, P = 0.03) with significant heterogeneity (I2 = 73%). The meta-regression showed that body mass index (BMI) of females was positively associated with the RR for the effect of probiotics on GDM (coefficient = 0.084, P = 0.01). The results of subgroup analyses also suggested that probiotics significantly reduced the risk of GDM in women with BMI < 26 kg/m2, but not in those with BMI ≥ 26 kg/m2 (P for subgroup difference = 0.001). In addition, the preventative efficacy of probiotics on GDM was remarkable in women < 30 years, but not in those ≥ 30 years (P for subgroup difference < 0.001). In conclusion, probiotics may be effective in reducing the risk of GDM, particularly for females with lower BMI and younger age.